1996
DOI: 10.1177/002221949602900603
|View full text |Cite
|
Sign up to set email alerts
|

Inner-City Adults with Severe Reading Difficulties

Abstract: Relatively little is known about the characteristics of inner-city adults who seek assistance from literacy programs. Increased knowledge about this population will enhance the development of more effective programs, as well as policy options. This study describes the characteristics of 280 adults, ages 16 to 63, who came to an adult literacy program that focused on severe reading difficulties. The program, located within a hospital complex in a large, urban area, attracted these individuals through an extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…Previous research has indicated that adult literacy students possess relative strength in the area of orthographic knowledge but serious deficits in the phonological domain (e.g., Bruck, 1993;Castro-Caldas, Petersson, Reis, Stone-Elander, & Ingvar, 1998;Fawcett & Nicholson, 1995;Gottesman, Bennett, Nathan, & Kelly, 1996;Lindamood, Bell, & Lindamood, 1992). The current study used error analysis to investigate further the phonological and orthographic processing differences that were observed by Greenberg et al (1997).…”
mentioning
confidence: 94%
“…Previous research has indicated that adult literacy students possess relative strength in the area of orthographic knowledge but serious deficits in the phonological domain (e.g., Bruck, 1993;Castro-Caldas, Petersson, Reis, Stone-Elander, & Ingvar, 1998;Fawcett & Nicholson, 1995;Gottesman, Bennett, Nathan, & Kelly, 1996;Lindamood, Bell, & Lindamood, 1992). The current study used error analysis to investigate further the phonological and orthographic processing differences that were observed by Greenberg et al (1997).…”
mentioning
confidence: 94%
“…Lastly, an American study by Gottesman et al (1996) measured the IQ of 280 students enrolled in an adult literacy program, using either the WAIS-R itself (Wechsler, 1981) or its Vocabulary, Information and Block Design subtests (scores converted according to the formula devised by Brooker & Cyr, 1986). The group's mean IQ was 81 (SD ¼ 12) which is way below the normal score.…”
Section: General Cognitive Skillsmentioning
confidence: 99%
“…As a result, we know that functional illiteracy is often associated with specific sociofamilial characteristics, or with inadequate instruction in learning to read (Bentolila, 1996;Gottesman, Bennett, Nathan, & Kelly, 1996;Purcell-Gates, Degener, Jacobson, & Soler, 2002). Many A-IL belong to ethnic minorities, or come from culturally and economically deprived backgrounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ainsi on sait que l'illettrisme est souvent associé à des caractéristiques sociofamiliales particulières ou à des méthodes d'apprentissage non adaptées (Bentolila, 1996;Gottesman, Bennett, Nathan & Kelly, 1996;Espérandieu & Vogler, 2000). Les personnes illettrées proviennent souvent des minorités ethniques, ou de milieux très défavorisés sur les plans économique et culturel.…”
unclassified